Using the 4 Pillars™ Practice Transformation Program to increase adolescent human papillomavirus, meningococcal, tetanus-diphtheria-pertussis and influenza vaccination. Issue 45 (27th October 2017) - Zimmerman, Richard K.; Raviotta, Jonathan M.; Nowalk, Mary Patricia; Moehling, Krissy K.; Reis, Evelyn Cohen; Humiston, Sharon G.; Lin, Chyongchiou Jeng
Abstract: Objectives: To report the results of an intervention using the 4 Pillars™ Practice Transformation Program (4 Pillars™ Program) to increase adolescent vaccinations including human papillomavirus vaccine (HPV) and influenza vaccines, which remain underutilized in this population. Study design: Eleven pediatric and family medicine practices, previously control sites from a randomized controlled cluster trial, with ≥50 adolescent patients participated. The 4 Pillars™ Program was the foundation of the intervention. De-identified demographic, office visit and vaccination data were derived from electronic medical record extractions for patients whose date of birth was 4/1/1997 to 4/1/2004 (ages 11–17 years at baseline). Vaccination rates for HPV, influenza, tetanus-pertussis-diphtheria (Tdap) and meningococcal (MenACWY) vaccines were determined for all eligible patients pre- and post intervention (i.e., vaccination rates on 4/1/2015 and 4/30/2016). Results: Among 9473 patients ages 11–17 years at baseline (4/1/2015), mean pre-intervention vaccination rates for HPV initiation and completion, meningococcal, Tdap and influenza vaccines were below national levels. Rates increased significantly post intervention ( P  < 0.001) for HPV initiation which increased 17.1 percentage points (PP) from 51.4%; HPV completion increased 14.8 PP from 30.7%, meningococcal vaccine uptake increased 16.6 PP from 79.1%, Tdap vaccine uptake increased 14.6 PP from 76.9%. Influenza vaccine uptake did not increase significantly (2.3 PP from 40.1%). In the regression using generalized estimating equations, odds of vaccination were higher for younger, non-white adolescents for all vaccines; being in a smaller practice decreased the odds of Tdap vaccination but increased the odds of influenza vaccination. Conclusion: Clinically and statistically significant improvements in HPV series initiation and completion, and meningococcal and Tdap vaccinations were observed in primary care practices implementing the 4 Pillars™ Practice Transformation Program. Clinical Trial Registry Number: NCT02165722.